On stage alone : soloists and the modern dance canon - Gitelman, Claudia; Palfy, Barbara (University Press of Florida, 2012)
"Soloists ignited the modern dance movement and have been a source of its constant renewal. Pioneering dancers such as Loïe Fuller, Isadora Duncan, Ruth St. Denis, and Maud Allan embodied the abstraction and individuality of the larger modernist movement while making astounding contributions to their art. Nevertheless, solo dancers have received far less attention in the literature than have performers and choreographers associated with large companies. In On Stage Alone, editors Claudia Gitelman and Barbara Palfy take an international approach to the solo dance performance. The essays in this standout volume broaden the dance canon by bringing to light modern dance soloists from Europe, Asia, and the Americas who have shaped significant, sustained careers by performing full programs of their own choreography. Featuring in-depth examinations of the work of artists such as Michio Ito, Daniel Nagrin, Ann Carlson, and many others, On Stage Alone reveals the many contributions made by daring solo dancers from the dawn of the twentieth century through today. In doing so, it explores many important statements these soloists made regarding topics such as freedom, personal space, individuality, and gender in the modern era"--Publisher's website.